(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study was carried out on six Iraqi breed rams, aged between 2 to 4 years, during the period fromNov. 2018 to the Mar. 2019. Semen samples were collected from each ram with electro ejaculator at themorning, one ejaculate per week over a time of 16 weeks. Pooled semen for all rams were used to evaluatethe characteristics of semen to avoid individual variation between the animals. The volume and the coloroffresh semen was recorded directly, then semen was evaluated for mass and individual motility, live/deadpercentage and sperm abnormalities. Semen samples were diluted 1:10 with a Tris-based extender, anddivided into seven parts (each part 2ml), 0.1µml, 1.0µml & 3.0µml concentration of melatonin were addedto the T1, T2 and T3 respectively, L-arginine were added to the T4, T5 and T6 in 0.001µmol, 0.1µmol and1.0µml concentration respectively while T7 serve as a control without any addition. All treatments cooled at4°c. Then semen parameters evaluated. It was concluded from this study that addition of 0.1 µmol melatoninsignificantly protected ram sperm cell from cold storage that induced negative effects on sperm function.However the addition of L-arginine have no beneficial effect on cooled ram semen.